Case studies on Marugame and IPMI Institute: To tackle on coaching performance - Irma M Nawangwulan; Samuel PD Anantadjaya; Sasotya Pratama; Abdul Haris Lahuddin; Daniella CE Samuel; DC Ethan Samuel; Timotius Agus Rachmat; Mohammad Wahiddudin (Universitas Pendidikan Indonesia, 2025)
This case study explores the strategic and operational practices of Marugame Udon and IPMI Institute. By analyzing both organizations through the lenses of interaction management, problem-solving, decision-making, team development, and coaching performance, the study uncovers practical insights into effective organizational behavior across different industries. At Marugame, the emphasis on lean operations and team coordination plays a critical role in ensuring customer satisfaction and operational efficiency. Through real-time interaction management and standardized communication protocols, Marugame fosters a service-oriented culture where frontline staff are empowered to solve problems and make quick decisions. Leadership coaching is implemented at the store level to improve service performance and employee retention. In contrast, IPMI Institute emphasizes strategic decision-making and collaborative learning in academic and administrative settings. The coaching culture at IPMI Institute fosters professional growth, critical thinking, and emotional intelligence among both staff and students. The findings highlight that both organizations, while operating in different sectors, leverage similar core principles of organizational development. Interaction management and coaching serve as the backbone for efficient teamwork and agile decision-making. This comparative case analysis underscores the value of context-specific adaptations of these practices, reinforcing the need for tailored leadership approaches in hospitality and education sectors. Abstrak Studi kasus ini mengeksplorasi praktik strategis dan operasional Marugame Udon dan IPMI Institute. Dengan menganalisis kedua organisasi melalui sudut pandang manajemen interaksi, pemecahan masalah, pengambilan keputusan, pengembangan tim, dan kinerja pembinaan, studi ini mengungkap wawasan praktis tentang perilaku organisasi yang efektif di berbagai industri. Di Marugame, penekanan pada operasi ramping dan koordinasi tim memainkan peran penting dalam memastikan kepuasan pelanggan dan efisiensi operasional. Melalui manajemen interaksi waktu nyata dan protokol komunikasi standar, Marugame menumbuhkan budaya berorientasi layanan di mana staf garis depan diberdayakan untuk memecahkan masalah dan membuat keputusan cepat. Pembinaan kepemimpinan diterapkan di tingkat toko untuk meningkatkan kinerja layanan dan retensi karyawan. Budaya pembinaan di IPMI Institute mendorong pertumbuhan profesional, pemikiran kritis, dan kecerdasan emosional di antara staf dan mahasiswa. Temuan tersebut menyoroti bahwa kedua organisasi, meski beroperasi di sektor yang berbeda, memanfaatkan prinsip inti pengembangan organisasi yang serupa. Manajemen interaksi dan pembinaan berfungsi sebagai tulang punggung kerja tim yang efisien dan pengambilan keputusan yang tangkas. Lebih jauh, analisis kasus komparatif ini menggarisbawahi nilai adaptasi spesifik konteks dari praktik-praktik ini, yang memperkuat perlunya pendekatan kepemimpinan yang disesuaikan di sektor perhotelan dan pendidikan. Kata Kunci: kapasitas manajerial; kapasitas teknis; keterampilan akademik; pengembangan keterampilan hidup; tugas operasional; tugas strategis